Involvement of Vitamin D in Chronic Infections of the Waldeyer`s Ring in the School Aged Child - VINTILESCU, BȘ (Curr Health Sci J, 2019)
Chronic infections of the Waldeyer`s lymphatic ring constitute a frequent pathology in school age, one of the pathogenic mechanisms involving low levels of vitamin D. In this study, we analyzed integrated the clinico-epidemiological aspects, the risk factors and the serum level of vitamin D for 51 school aged children who presented chronic inflammation in various levels of the Waldeyer`s ring. Most inflammations were present in females patients (80.4%), from the urban areas (66.6%), being localized in palatine tonsils (64.7%), in patients with deficient prophylaxis of hypovitaminosis D (68.6%) and low serum levels of vitamin D (72.5%). The results highlight the importance of maintaining a normal status of vitamin D, especially in recurrent infectious context.